Cómo afrontar lo inesperado. La fuerza mayor en la contratación internacional: ¿principio o cláusula? - Castro Ruiz, Marcela (2015)
Force majeure excludes civil liability and is accepted as a universal defense in accordance with the principle that nobody is bound to perform what is impossible. In the civil law systems force majeure is a concept provided for by statutory law, leaving its application to the courts in a case by case approach. In the common law system, the contract is terminated and the non-performing party is exempted from paying damages if there is an emerging event which frustrates the purpose of the contract or renders the same as commercially impracticable. The force majeure defense can be invoked only if there is an express contractual provision where the parties define which events are deemed as force majeure and agree upon its legal effects. This paper examines the interaction between the two systems, which happens most significantly in the international business transactions.